Active dynamic thermography method for TRAM flap blood perfusion mapping in breast reconstruction. Issue 2 (3rd July 2017) - Moderhak, M.; Kołacz, Sz.; Jankau, J.; Juchniewicz, T.
Abstract: This paper presents the new method of the transverse rectus abdominis musculocutaneous flap blood perfusion mapping based on the active dynamic thermography. The method is aimed at aiding a surgeon during breast reconstruction procedure. A pair of d T norm and t 90_10 parameters were used as parametric image descriptors of the flap blood perfusion. The method was tested on 38 patients that were subjected to breast reconstruction procedure. This showed that, comparing to the static thermography, this is potentially an objective and effective method of skin flap perfusion assessment that can be performed in the operating room.